Improving the reproducibility of size distribution of protein crystals produced in continuous slug flow crystallizer operated at short residence time - Pu, Siyu (2021)
Continuous crystallization of proteins at short residence time and high supersaturation level is attractive in terms of the space-time yield and production efficiency. Nevertheless, it is rarely pursued due to its less-than-desirable crystal size distribution (CSD) characterized by the abundance of small crystals due to high nucleation rate. The small crystals were prone to random agglomeration, resulting in poor crystals’ residence time distribution, hence low CSD's reproducibility. Herein we developed a segmented slug flow crystallizer (SFC) design operated at short residence time (<30 min) comprising a short nucleation segment and a growth segment operated at different temperature and fluid velocity. The SFC design improved the CSD's reproducibility by limiting small crystals and large-sized agglomerates formations as evidenced by the small coefficient-of-variations between replicates (<10%). Lysozyme crystals having size of roughly 13–14 µm with well-preserved bioactivity were produced at yield and space-time yield of approximately 67% (w/w) and 93 g/L·h, respectively.